Formation of the Golden Generation of Indonesia with Religious Character Through the Habituation of Kultum at UPT SDN Sidorejo 1 - Badri Atul Fikriyah; Linda Melina Putri; Barokatul Puji Lestari; Wendri Wiratsiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article was created as an effort to publish about the habits carried out by students in order to form character by using the method of habituation of kultum every Thursday. Personality education obtained by children from their daily activities is often irregular and less systematic, therefore the habituation of kultum is used as one of the programs that are expected to be able to create a golden generation with a religious character. Therefore, it is very important to choose the right and appropriate habits so that they can form the religious character of the golden generation of Indonesia. The method used in this study is a qualitative approach with data collection techniques using a library study approach or can be called library research, in which the author collects various references through journals, articles, and other sources. And from this study, appropriate strategies can be identified to improve religious literacy. Through the habituation of kultum every Thursday, the character that is expected to emerge in students of UPT SDN Sidorejo 1 is a religious and civilized character.